Creolization and contact - Smith, Norval; Veenstra, Tonjes, 1962- (Creole language library ;, 2001)
This volume contains revised and extended versions of a selection of the papers presented at "The Amsterdam Workshop on Language Contact and Creolization." These studies apply the concept of relexification to creoles as well as other contact languages; highlight the relevance of strategies of second language learning for theories of pidgin/creole genesis; critically discuss the notions levelling (koine formation) and convergence; the relation between types of contact situations and processes of crosslinguistic influence; as well as the linguistic consequences of the social structure of the pla.